Low-energy architecture: From theory to design - Serghides, Despina Kyprianou (My University, 2015)
This introduction projects the potential application of bioclimatic design interwoven with the objective of energy efficiency and the utilization of renewable energy resources for indoor comfort. This is, nowadays, of particular interest for all countries, since architecture is currently influenced beyond the usual functional, cultural and technological constraints by the incidence of rapid urban development and huge tourist inflows. This often results to standardized "international architecture" with high-technology services and catastrophic ecological and cultural consequences. Sadly, these international designs rely mostly on mechanical means, with high consumption of energy, ignoring the local tradition of climatic design, which respects the environment and reflects the thread of continuity, coherence and local flavour. Bioclimatic architecture considers the building totally from the stage of its inception as a place of energy exchange between the indoor and the external environment, natural and climatic. It considers the building as a living organism; a dynamic structure which utilizes the beneficial climatic parameters (solar radiation for winter, sea breezes for summer) whilst avoiding the adverse climatic effects (cold winds for winter, solar radiation for summer). It is precisely the approach to this challenge of bioclimatic, energy-efficient architecture, posed to every designer as the coordinator of multiple considerations that is to be presented and discussed during this introduction. The main heating and cooling strategies are outlined and their adoption in the design process is approached in four stages from site planning, orientation and shape, layout and envelope of the building. These aspects are illustrated with the "Bioclimatic Designs for the Student Housing of the New University Campus of Cyprus", for which the author was the bioclimatic consultant, and the first phase of buildings for the University of Cyprus (Architect A. Kyprianou & Associates), to indicate how bioclimatic techniques address the problems of thermal and optical control.